PRILAKU KELUARGA SADAR GIZI (KADARZI) TERHADAP KEJADI AN STUNTING PADA BALITA - Mailiza Cahyani (JOMIS (Journal of Midwifery Science), 2023)
Families are said to be in good Kadarzi behavior when they adhere to five indicators, namely being weighed regularly, exclusive breastfeeding, eating a variety of foods, using iodized salt and using food supplements. Deformity is a disease caused by an imbalance in nutrition during the golden age, not a growth hormone abnormality or due to certain diseases. The aim of the study was to determine the relationship between the behavior of a family who is aware of nutrition (kadarzi) and the incidence of stunting in toddlers at the Rejosari Health Center in Pekanbaru. The type of quantitative research with a cross-sectional design is to examine the relationship between the behavior of families who are aware of nutrition and the incidence of stunting in toddlers at the Rejosari Health Center, Pekanbaru City. This research was conducted at the Rejosari Health Center in Pekanbaru City, which was held from March to August 2022. The population in this study were all mothers who had babies at the Rejosari Health Center, Pekanbaru City, totaling 250 people. The sample is 154 people. From the results of the study it can be concluded that the behavior of families who are aware of nutrition at the Rejosari Health Center in Pekanbaru is less than 97 people (63%) and the behavior (level) of families who are aware of adequate nutrition. for 57 people (37%). At the Rejosari Health Center in Pekanbaru, 81 people (52.6%) and 73 people (47.4%) had growth problems. The results of the analysis obtained a p-value of 0.020 and the coefficient (OR) = 2.198, so this means that there is a relationship between the behavior of families who are aware of nutrition (kadarzi) and the incidence of stunting in toddlers at the Rejosari Health Center in Pekanbaru City. It is hoped that the officers can provide counseling and counseling to the public about family behavior that is aware of diet and its relationship to stunting.